A comprehensive review on ecological approaches of waste to wealth strategies for production of sustainable biobutanol and its suitability in automotive applications. (1st July 2021) - Karthick, C.; Nanthagopal, K.
Highlights: Notable stages in the history of butanol production are outlined. Efficacy biobutanol production methods are summarized with various biomass sources. Upstream processes have been initialed for efficient production of butanol. Suitability of butanol for SI and CI engine applications are presented. Techno-economic analysis of butanol is emphasized to enhance large scale production. Abstract: Biobutanol has been emerging as a sustainable biofuel due to its superior form of heat content, sustainable volatility, better anti corrosive nature and more importantly low moisture content. The waste resources utilization for biobutanol production has sustainability and economic feasibility due to their easier availability and landfilling nature. The foremost limitations in the biobutanol development are lower yield rate, unavailability of feedstock and inhibitor formation. These obstacles are easily exterminated by the appropriate selection of waste biomass resources, few advanced metabolic engineering techniques and recent developments on integrated bioprocessing strategies with effective solvent recovery and purification methods. This review has been made to elaborate the various production techniques that have been enriched on biobutanol production from all the existing waste resources in last one decade and the highlights the research progress on biobutanol suitability in automotive applications. An elaborative discussion are undertaken on selection of waste feedstocks, superior pretreatment processes, selection of optimum strain, metabolic pathways of various microbes and separation techniques to enhance the economical biobutanol fermentation process. In a second phase of the review, the properties assessment of biobutanol and its technical suitability in spark ignition and compression engine are discussed in terms of performance, combustion and emission aspects. In the end, techno-economic analysis on biobutanol production is also provided to improve the commercial eminence on developing advanced techniques. Finally, the review report provided the route map towards the importance of developing efficacy integrated production techniques, research emphasis on flex fuel operation of biobutanol in hybrid configuration vehicles to meet the global demand in future.